An Analysis of Teaching Strategies on Students’ English Language Learning at MTsN 1 Kota Bengkulu - Saputra, Yogy Ardian; Zasrianita, Fera; Pebriani, Hanura (TOFEDU: The Future of Education Journal, 2025)
This study addressed the limited research on analysis of teaching strategies on students’ English language learning at MTsN 1 Kota Bengkulu. It aims to investigate how the teachers’ experience and students’ perception about teaching strategies employed towards the students English language learning. A mixed-method design was employed, combining qualitative approaches (interviews, documentation) and quantitative data (questionnaires) involving 36 ninth-grade students and a teacher at MTsN 1 Kota Bengkulu. The findings indicate that the teaching strategies using a combination of project-based learning, peer tutoring, mini-projects, and interactive activities such as Text Songs and outdoor activities implemented in ninth-grade MTs English classes have a positive impact on students’ English language learning. In addition, students responded positively showing increased enthusiasm, active participation, greater collaboration, and they also expressed that these strategies made learning more enjoyable, less monotonous, and easier to understand, while boosting confidence and willingness to participate.